Optimization and Life cycle Cost Analysis of Renewable Energy Supply Options for Academic Buildings- A Case Study - Paragond, Laxmanrao Rao S.; Kurian, Ciji Pearl; Singh, B.K. (International Journal of Energy Economics and Policy, 2019)
In this paper focuses on realizing alternate power supply sources to the Academic buildings located at Manipal, Karnataka. India, and analyzing the possible combination of the Hybrid Energy sources. The main emphasis is on steering the Optimization and Life Cycle Cost (LCC) analysis of the Hybrid Energy sources. The Hybrid Energy System optimization and feasibility study are carried out using HOMER Software and the results are verified with Linear Programming. The case study is conducted with the involvement of PV, Wind turbine and Diesel Generator (DG) along with the battery bank. Further, the DG was integrated with the renewable energy sources to smoothen the power circulation and enhance the reliability issues. The realistic climate data obtained from the NASA website for the location Manipal (13.347° N, 74.75° E) and estimates the solar and wind power using the models developed Keywords: PV, Wind, LCC, Optimization, HOMER JEL Classifications: Q21, Q40, Q41 DOI: https://doi.org/10.32479/ijeep.7890